Lymphocytic Infiltration Of Jessner-An Unusual Presentation - Krishnan SGS; Yesudian Devakar P; Jayaraman M; Janaki V. R; Boopal Raj J.M (Wolters Kluwer Medknow Publications, 1999)
A 45 year old male presented with an erythematous plaque involving the entire face and extending on to the front of neck of 23 years duration, without any history of remission of exacerbation. A skin biopsy revealed collection of lymphocytes in the dermis without follicle formation, around the blood vessels and appendages, consistent with histopathology of jessnerâ€s lymphocytic infiltration. Patient responded dramatically to chloroquine with flattening of the lesion within 2 months.